Effectiveness of a new means of etiotropic therapy of mastits in cows during the lactation period - Stetsko, Taras; Ostrovska, Larysa; Kostyschyn, Yevhen; Katsaraba, Orest; Kostyshyn, Lidiia-Mariia; Morozenko, Dmytro (ScienceRise: Biological Science, 2023)
The aim: is to study the therapeutic effectiveness of the new veterinary medicinal product Revozyn RTU 400 mg/ml (suspension for injections), manufactured by Eurovet Animal Health B.V. (Netherlands), in the treatment of acute (clinical) and hidden (subclinical) mastitis in cows during lactation. Materials and methods. The research was conducted on dairy cows of the Simmental breed with a milk productivity of 6000-6500 kg of milk per lactation (F "Pchany-Denkovich", Pchany village, Stryi district, Lviv region). To confirm the diagnosis of "acute mastitis" and to identify cows with hidden (subclinical) mastitis, as well as to establish the effectiveness of the researched drug after treatment, a sample was taken with the California Mastitis Test (CMT), manufactured by Bayer Animal Health GmbH, Germany. For bacteriological research, milk samples were taken from the affected quarters of the mammary gland (1 sample from each cow) in compliance with generally accepted sanitary rules. The sensitivity of bacterial isolates to the drug was determined by diffusion in agar using standard discs with benzylpenicillin. Results. A clinical examination of 127 Simmental dairy cows of different periods of lactation was carried out. During the clinical-diagnostic examination of animals, 8 cows with clinically pronounced, acute course of mastitis were found. According to the nature of the exudate in 3 cows, mastitis was serous, in 5 cows it was purulent-catarrhal. For serous mastitis, the CM test gave a positive result – thickening, the milk solution looks like a gel. In case of purulent catarrh, a sample with the CMT gave a strongly positive result – the mixture thickened, the gel took on a certain shape and became very viscous. The CMT revealed 12 cows with suspected latent mastitis. Representatives of opportunistic microflora – Streptococcus agalactiae, Staphylococcus aureus, and Escherichia coli bacteria were isolated and identified from mastitis milk. The summarized results of the clinical trial of the drugs Revozyn RTU 400 mg/ml and Procillin® 30 % on cows suffering from the clinical form of mastitis were as follows. On the 10th day of the experiment, a milk sample with the California mastitis test showed that all milk samples from cows of both groups (with the exception of one milk sample from a cow from the control group) gave a negative result (the solution remained liquid, blue or gray and homogeneous, without clots). Taking into account the results of the CMT and the number of somatic cells in the milk after the therapy, the therapeutic effectiveness of the veterinary medicinal product Revozyn RTU 400 mg/ml in the treatment of various forms of mastitis in lactating cows was 100 %, and the one of the comparative drug Procillin® 30 % was 83.3 % . Conclusions. A clinical study of the veterinary medicinal product Revozyn RTU 400 mg/ml, suspension for injections, manufactured by Eurovet Animal Health B.V. (Netherlands) established its effectiveness in the dosage, recommended by the manufacturer, in the treatment of clinical and subclinical mastitis in lactating cows, caused by microorganisms sensitive to benzylpenicillin. In terms of therapeutic effectiveness, the drug Revozyn RTU 400 mg/ml was not inferior to the comparative drug Procillin® 30 % in its dosage form and active substance when used in the treatment of various forms of mastitis in lactating cows